ALKİL METAKRİLATLARIN GLİSİDİLMETAKRİLAT İLE KOPOLİMERLERİNİN SENTEZİ VE KARAKTERİZASYONU - Soykan, Cengiz; İlter, Zülfiye (Erciyes Üniversitesi, 2001)
Bu çalışmada, glisidilmetakrilatın (GMA), 1,4-dioksan çözeltisinde 60°C'de benzoilperoksitin başlatıcı olarak kullanılmasıyla alkil metakrilatlar ile kopolimerleri hazırlandı. Kopolimerlerin yapısı FT-IR, 1H-NMR ve 13C-NMR teknikleriyle karakterize edildi. Kopolimerlerin çözünürlük parametreleri ve yoğunlukları sırasıyla titrasyon ve yüzdürme metotlarıyla belirlendi. Kopolimerlerin camsı geçiş sıcaklıkları ve molekül kütleleri DSC ve GPC ölçümleriyle belirlendi. TGA çalışmaları ile kopolimerlerin sıcaklıkla bozunmalarındaki depolimerizasyon aktivasyon enerjileri (Ea) hesaplandı

In this work, copolymers of glycidylmethacrylate (GMA) were prepared with alkyl methacrylates in 1,4-dioxane solution at 60°C by using benzoylperoxide as initiator. The structures of copolymers were characterized by FT-IR, 1H-NMR and 13C-NMR techniques . The solubility parameters and densities of copolymers were determined by titration and flotation methods, respectively. The glass transition temperatures and molecular mass of copolymers were determined by DSC and GPC measurements. The activation energies (Ea) on the thermal decomposition of copolymers were calculated by TGA studies
SYNTHESIS AND CHARACTERIZATION OF COPOLYMERS OF ALKYL METHACRYLATES WITH GLYCIDYL METHACRYLATE